'God desires ease for you, and desires not hardship for you': a comparison of Qur'anic and Judaeo-Christian law - Franzmann, Majella (Routledge, 2010)
This article provides an overview of law within the First Testament and the Qur'an. It focuses in particular on the Decalogue/Ten Commandments within the First Testament and its influence on the traditions of Judaism and Christianity, and beyond that to Western culture in general. The study of law in the Qur’an investigates the form of prescriptions typified by Surah 2:183–187. Although the overview of both traditions raises some common themes, it is proposed that the Qur’an offers a unique approach to law by its understanding of, and allowance for, human nature.